مساهمة في دراسة التأثير العصبي الودي وشبه الودي على معدل ضربات قلب الضفدع Rana Esculenta (Latakia University Journal -Basic Sciences Series, 2018)
تختلف العضلات الهيكلية عن العضلة القلبية بنيوياً ووظيفياً حيث أن العضلة القلبية تعمل ذاتياً بإشراف الجملة العصبية الإعاشية vegetative nervous system الودية وشبه الودية . إن التسرب البطيء لشوارد الصوديوم  إلى الوسط داخل الخلوي للألياف القلبية الإستثارية  من شأنه أن يجعل عتبة التنبيه كافية لإزالة الاستقطاب وبدء كمون الفعل القلبي المعروف . تهدف هذه الدراسة إلى تأكيد دور الأستيل كولين (شبه ودي )والأدرينالين (ودي) على معدل  نبضات قلب الضفدع حيث لاحظنا أن الأستيل كولين يقلل والأدرينالين يزيد تلك النبضات، وذلك باستخدام تراكيز مختلفة (0.001 – 0.1 mg / ml) من تلك المادتين فضلا عن مواد أخرى مشابهة في التأثير. Cardiac muscle differs from skeletal muscles both structurally and functionally. The most striking feature of its contractility is that it is able to initiate its own rhythmic contractions .This is due to leaky cell membranes ,in which calcium and sodium ions slowly leak into the cells. This leaking causes a slow depolarization to the thre shold ,so that  an action potential  can be formed and contraction of cardiac muscle is initiated. The object of our study was to emphasize the effect of the role of acetylcholine and adrenaline on the heart beat. Our results demonstrate that  acetylcholine decreases heart beat where adrenaline increases it. We used different concentrations of both compounds  (0.001 – 0.1 mg / ml ), and others that have the same effects.